Board Diversity and Agency Cost: Evidence from Bursa Malaysia Stock Exchange - Mohd Waliuddin, Mohd Razali; Najihah, Mohd Nasir; Shazali, Shaharudin (OPRA Publications, 2023)
This study aims to determine how board diversity affects agency costs in Malaysia. The sample of 395 firms listed on Bursa Malaysia from 2014 to 2016 was examined in this study. All non-financial data were collected from the annual report, and financial data were composed of DataStream. Increasing board size and board independence decreases the agency's cost. This bigger board size and more independent directors enhance better monitoring of agency costs. Future researches suggest this study can be extended using more sample and period of study and using other countries' data.